Tourism in protected areas: constraints and challenges - Mat Som, Ahmad Puad; Mohamed, Badaruddin; Wong, Kong Yew (Tourism Educators Association of Malaysia, 2006)
The importance of protected areas in tourism and their contribution to the economy and regional development of a country has been well-documented. However, the size of protected areas is shrinking due to demand of development as the number of visitors continues to increase and the adverse impacts on the environment continues to deteriorate. Hence, the success in managing tourism in protected areas is dependent upon many factors and is often influenced by several external factors. As the literature argues that there are often gaps in the capability to effectively manage parks and protected areas, this paper attempts to explore constraints and challenges in developing tourism in protected areas in developing countries particularly in Malaysia.